Early life trauma, depression and the glucocorticoid receptor gene – an epigenetic perspective. Issue 16 (21st September 2015) - Smart, C.; Strathdee, G.; Watson, S.; Murgatroyd, C.; McAllister-Williams, R. H.
Abstract : Background: Hopes to identify genetic susceptibility loci accounting for the heritability seen in unipolar depression have not been fully realized. Family history remains the 'gold standard' for both risk stratification and prognosis in complex phenotypes such as depression. Meanwhile, the physiological mechanisms underlying life-event triggers for depression remain opaque. Epigenetics, comprising heritable changes in gene expression other than alterations of the nucleotide sequence, may offer a way to deepen our understanding of the aetiology and pathophysiology of unipolar depression and optimize treatments. A heuristic target for exploring the relevance of epigenetic changes in unipolar depression is the hypothalamic–pituitary–adrenal (HPA) axis. The glucocorticoid receptor (GR) gene ( NR3C1 ) has been found to be susceptible to epigenetic modification, specifically DNA methylation, in the context of environmental stress such as early life trauma, which is an established risk for depression later in life. Method: In this paper we discuss the progress that has been made by studies that have investigated the relationship between depression, early trauma, the HPA axis and the NR3C1 gene. Difficulties with the design of these studies are also explored. Results: Future efforts will need to comprehensively address epigenetic natural histories at the population, tissue, cell and gene levels. The complex interactions between the epigenome, genome and environment, as well as ongoing nosological difficulties, also pose significant challenges. Conclusions: The work that has been done so far is nevertheless encouraging and suggests potential mechanistic and biomarker roles for differential DNA methylation patterns in NR3C1 as well as novel therapeutic targets.